Joint Cost Allocations – Proceedings of the University of Oklahoma Conference on Cost Allocations, April 23, 24 1981 (Book). - Meyer, Philip E. (The Accounting Review, 1982)
Reviews the book "Joint Cost Allocations-Proceedings of the University of Oklahoma Conference on Cost Allocations, April 23, 24, 1981," by Shane Moriarity.